Molecular identification and parasite-host interaction of hybrids of the genus Piaractus in the upper Paraná River. - Cavalcanti, Lidiany Doreto (2024)
Hybridization is the interspecific crossing of species with the potential to optimize zootechnical indices, and this is a common practice in fish farming. However, inadequate management and facilities lead to escapes and fish settling in natural environments, with the possibility of impacts on local biocenoses. Little is known about genetic damage and parasite-host interactions in the case of hybrid escapes. The aims of this thesis are: i) to identify the fish morphologically collected as pacu (P. mesopotamicus) in the upper Paraná River using molecular markers such as: mitochondrial COI (cytochrome C oxidase, subunit I) and nuclear TROP (α-tropomyosin); ii) to evaluate parasite-host interactions for hybrids and their parents that coexist in the same environment, using network analysis through the metrics of modularity and nesting and then recalculating these metrics after the removal of pure and native individuals (P. mesopotamicus). The fish were identified as P. mesopotamicus, P. brachypomus, first generation hybrids (F1) with mitochondrial DNA (mtDNA) from P. brachypomus and nuclear DNA (nDNA) from P. mesopotamicus and P. brachypomus and advanced hybrids with mtDNA from P. brachypomus and nDNA from P. mesopotamicus. Regarding parasite-host interactions, the network metrics showed a tendency towards a decrease in modularity and nestedness for general and ectoparasite networks and an increase for endoparasites, after the removal of P. mesopotamicus, showing that native individuals have interactions that alter network metrics. Regarding cascade extinctions, there were no differences between hosts. This study reinforces the importance of research into hybrids in natural environments and raises concerns about genetic contamination, vulnerability to infection/infestation by parasites, and the local decline of native species, which are important for fishing and subsistence.